The Public Services After Covid-19 at the Occupational Health General Hospital in West Java Province - Wulandari Atur Rejeki, Putri; Fathurrahman Syaban, Muhammad; Akbar, Ali (Indonesian Association for Public Administration (IAPA), 2024)
One of the public service delivery institutions in the health sector in the Province of West Java is the Occupational Health Regional General Hospital (RSKK). This class D hospital offers emergency care, inpatient care, and outpatient care. Based on five aspects of service quality—tangible, reliability, responsiveness, assurance, and empathy—the research attempts to provide an understanding of the public services offered by the RSKK. A quantitative descriptive research design was adopted. The population were all patients at the RSKK. One hundred respondents were selected between April and July of 2024 using the Accidental Sampling technique. The primary data used to measure patient satisfaction with service quality. By distributing questionnaires, the data collecting method was implemented. The Customer Satisfaction Index was employed for data analysis. The study's findings indicate that only one dimension—the tangible, which has a value of 71.34%— expressing satisfaction. The criteria for the other four dimensions, expressing moderate levels of satisfaction, with values of 64.96% for the reliability, 60.67% for the responsiveness, 65.20% for the assurance, and 59.81 for the empathy. In summary, the RSKK public service representation does not yet reflect a high enough level of quality. To maintain growing patient satisfaction, performance must be improved in every area of service quality.